Evidence for a regulated Ca2+ entry in proximal tubular cells and its implication in calcium stone formation - Ibeh, Cliff Lawrence (2019)
Fil: Ibeh, Cliff-Lawrence. Veterans Affairs Medical Center. Research Service Center. Calcium Signaling Laboratory; Estados Unidos